STUDIES ON THE SENSITIZATION OF ANIMALS WITH SIMPLE CHEMICAL COMPOUNDS - Landsteiner, K. (The Rockefeller University Press, 1935)
Experiments on the sensitization of guinea pigs with simple chemical compounds are described. Positive effects were obtained by the administration of small quantities, namely fractions of milligrams, with 1:2:4 chlorodinitrobenzene, p-nitrosodimethylaniline, 1:2:4 trinitrobenzene, picryl chloride, four dichlorodinitrobenzenes, and a number of other aromatic compounds. Several substances chemically similar to those enumerated gave negative results. The first named compound is known to produce hypersensitiveness in human beings, a large number of cases having been observed in factory workers. The mechanism of these effects is discussed.